Wernicke encephalopathy in combination with acute polyneuropathy under the guise of a demyelinating disease in a teenager with an eating disorder - E. O. Ovchinnikova; A. S. Kotov; M. V. Panteleeva; E. V. Mukhina (Русский журнал детской неврологии)
Wernicke encephalopathy is a neuropsychiatric syndrome characterized by three main symptoms: oculomotor disturbances, cerebellar ataxia, and psychiatric disturbances. The condition is associated with a high mortality and morbidity rate. Wernicke encephalopathy is most commonly seen in adolescent children presenting with a vitamin B1 deficiency. Thiamine deficiency may also cause polyneuritis syndrome, with or without the aforementioned symptoms. The condition is characterized by sensory-motor impairments in a symmetrical pattern, dysarthria, and paresis or even paralysis of the lower limbs. This report focuses on an adolescent case presenting acute oculomotor paresis, nystagmus, leg weakness, impaired gait, decreased deep tendon reflexes, cognitive impairment, and a history of recurrent vomiting, prolonged starvation, and eating behaviour disorders. The magnetic resonance imaging scan reveals symmetrical pathological foci of increased intensity in T2 in the periaqueductal region, at the Magendie’s central aperture. The patient displays a mixed motor-sensory polyneuropathic syndrome affecting both lower limbs, primarily of the axonopathy type, based on electroneuromyography data. Positive outcomes such as restored eyeball movement, enhanced gait, increased muscle strength in the lower legs and feet, and better management of sensory disorders have occurred due to thiamine treatment.